The Effect of Influencer Marketing on Purchase Intention: The Mediating Role of Influencer Credibility among Instagram and TikTok Users in Solo Raya - Ajietama Imam Wiyoga; Imfrianti Augtiah (Golden Ratio of Mapping Idea and Literature Format, 2026)
The rapid growth of social media platforms has led firms to increasingly adopt influencer marketing as a strategic digital marketing approach to shape consumer behavior. This study aims to empirically investigate the influence of influencer characteristics namely expertise, trustworthiness, likability, information quality, and entertainment value on consumers’ purchase intention, with influencer credibility serving as a mediating variable. A quantitative research approach was employed using a survey method. Data were collected through an online questionnaire administered to 286 active Instagram and TikTok users in the Solo Raya region, Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the proposed research model and hypothesized relationships. The results reveal that all examined influencer characteristics have a positive and significant effect on influencer credibility. Moreover, influencer credibility is found to positively and significantly influence consumers’ purchase intention. The mediation analysis further confirms that influencer credibility plays a significant mediating role in the relationship between influencer characteristics and purchase intention. These findings highlight the crucial role of influencer credibility in strengthening the effectiveness of social media–based marketing strategies, particularly in driving consumers’ purchase intentions.